Conserving Freshwater and Coastal Resources in a Changing Climate. - Grubin, Elizabeth.; Hardy, Abigail.; Lyons, Regina.; Schmale, Amelia.; Sugii, Takeo. (Tufts University. Tisch Library., 2018)
2007 M.A. in Urban and Environmental Policy and Planning Field Project. Client: The Nature Conservancy.